The societal cost of modifiable risk factors in Singapore - Vanessa Tan; Julian Lim; Katika Akksilp; Wai Leng Chow; Stefan Ma; Cynthia Chen (BMC, 2023)
Abstract Background Singapore is one of the most rapidly ageing populations in the world. Nearly half of all disease burdens in Singapore are attributable to modifiable risk factors. This indicates that many illnesses are preventable by modifying behaviours such as increasing physical activity levels or maintaining a healthy diet. Prior cost-of-illness studies have estimated the cost of selected modifiable risk factors. However, no local study has compared costs between groups of modifiable risks. This study aims to estimate the societal cost attributable to a comprehensive list of modifiable risks in Singapore. Methods Our study builds on the comparative risk assessment framework from the Global Burden of Disease (GBD) 2019 study. A top-down prevalence-based cost-of-illness approach was undertaken to estimate the societal cost of modifiable risks in 2019. These include healthcare costs from inpatient hospitalisation and productivity losses from absenteeism and premature mortality. Results Metabolic risks had the highest total cost of US$1.62 billion (95% uncertainty interval [UI] US$1.51-1.84 billion), followed by lifestyle risks of US$1.40 billion (95% UI US$1.36-1.66 billion) and substance risks of US$1.15 billion (95% UI US$1.10-1.24 billion). Across the risk factors, the costs were driven by productivity losses, heavily skewed towards the older working-age group and among males. Most of the costs were driven by cardiovascular diseases. Conclusion This study provides evidence of the high societal cost of modifiable risks and highlights the importance of developing holistic public health promotion programmes. As modifiable risks often do not occur in isolation, implementing effective population-based programmes targeting multiple modifiable risks has a strong potential to manage the cost of the rising disease burden in Singapore.